GAME-BASED LEARNING AS AN EFFECTIVE PEDAGOGICAL STRATEGY IN ENGLISH AS A FOREIGN LANGUAGE INSTRUCTION - Normo’minova Manzura Tolmas qizi (Sciental Journals Publishing, 2025)
This article examines the role of game-based learning as an innovative pedagogical strategy in teaching English as a Foreign Language (EFL). Rather than viewing games merely as recreational activities, the study emphasizes their instructional value in enhancing learners’ motivation, communicative competence, and cognitive engagement. The article analyzes the theoretical foundations of game-based learning, its impact on language skills development, and its contribution to learner-centered education. Special attention is given to how games facilitate meaningful interaction, reduce affective barriers, and support long-term language retention. The findings suggest that well-structured educational games significantly improve the effectiveness of English language instruction and promote a positive learning environment.
Keywords: Game-based learning, EFL instruction, language acquisition, learner motivation, communicative competence, interactive pedagogy